PROFESSIONAL FORMATION OF THE FUTURE SPECIALIST: PSYCHOLOGICAL FACTORS IN THE DEVELOPMENT OF TOLERANCE TO UNCERTAINTY - Kokarieva, Anzhelika; Luzik, Elvira; Ladohubets, Nataliia; Mykheieva, Tamara (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2022)
The article analyzes the process of professional specialists formation, which is determined by the psychological factors of the tolerance development of higher education students to uncertainty. The authors of the article prove the importance of taking into account personality properties that are basic, stable, permanent over time, that affect the professional development of a future specialist and play a significant role in assessing the likely results of decision-making in situations of uncertainty. The purpose of the article is theoretical substantiation and empirical study of psychological factors in the development of tolerance to uncertainty. The tasks of research are focused on the scientific substantiation of the concept "tolerance to uncertainty"; identification of psychological factors in the development of tolerance to uncertainty; analysis and interpretation of research results regarding the development of tolerance to uncertainty. The results of research proved that students of higher education, who have developed a high level of tolerance to uncertainty, are able to make alternative, creative and non-standard decisions, gain new experience even under conditions of uncertainty. Applicants of higher education possessing a feature of competence, are ready for creativity, experiments, improvisation. Higher education students, who have developed an average level of tolerance to uncertainty, are ready to work in conditions of lack of information, gaining new experience, ready for news, for solving complex tasks. Conclusions. Summarizing the results of the research on the development of tolerance to uncertainty, we rely on a personality trait, the psychological essence of which is resistance to the effects of the factor of uncertainty, vagueness of the environment and is manifested in the acceptance of ambiguity during the search for decision alternatives; tolerant attitude to novelty, variability and complexity of situations, to unpredictability. It has been proven that situations of uncertainty, which are a source of individual activity, contribute both to the formation of positive motivation for research activities and the need for special training of higher education students for professional actions in situations of uncertainty, thus contributing to their further professional development